CONTEMPORARY PRACTICES OF PUBLIC AUTHORITIES’ COOPERATION AT THE CENTRAL AND LOCAL LEVEL - Khashiyeva L.V. (Pressing Problems of Public Administration, 2018)
The article is devoted to the study of features of contemporary models of cooperation between publicauthorities at the central and local level in the foreign countries. Possible ways of application of thebest practices at the context of local government reform in Ukraine are defined.